2016
DOI: 10.1161/circulationaha.116.021727
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common arrhythmia encountered by cardiologists and is a major cause of morbidity and mortality. Risk factors for AF include age, male sex, genetic predisposition, hypertension, diabetes mellitus, sleep apnea, obesity, excessive alcohol, smoking, hyperthyroidism, pulmonary disease, air pollution, heart failure, and possibly excessive exercise. The management of AF involves decisions about rate versus rhythm control. Asymptomatic patients are generally managed with rate contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 92 publications
(120 reference statements)
0
12
0
1
Order By: Relevance
“…Bunch et al [12] evaluated the chronicity of AF and gender and concluded that gender did not influence the outcomes/need for reablation whereas the chronicity of AF did. Natale and colleagues, in a recent review of AF ablation, describes the “ideal patient with highest likelihood of procedural success” [13]. This patient would have only paroxysmal AF, no cardiac disease, and a nondilated left atrium [13].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bunch et al [12] evaluated the chronicity of AF and gender and concluded that gender did not influence the outcomes/need for reablation whereas the chronicity of AF did. Natale and colleagues, in a recent review of AF ablation, describes the “ideal patient with highest likelihood of procedural success” [13]. This patient would have only paroxysmal AF, no cardiac disease, and a nondilated left atrium [13].…”
Section: Discussionmentioning
confidence: 99%
“…Natale and colleagues, in a recent review of AF ablation, describes the “ideal patient with highest likelihood of procedural success” [13]. This patient would have only paroxysmal AF, no cardiac disease, and a nondilated left atrium [13]. However, patients who do not meet the mentioned criteria might also benefit from the procedure; this includes patients with HF [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations